Habitat Reduction and Population Structure of Endangered Asian Arowana (Scleropages formosus) Golden Red in Riau Sumatra, Indonesia - Anthonius Purnama, Arief; Masunaga, Tsugiyuki (Bogor Agricultural University, Indonesia, 2025)
This research was conducted in the arowana golden red Conservation Area (AgrCA) in Riau Province Rokan Hulu Regency, Sumatra, Indonesia from 2020 to 2023. The primary objective was to elucidate the population structure of arowana golden red in the midst of ongoing habitat degradation resulting from land use changes in AgrCA. Land use changes were analyzed by satellite imagery through the QGIS application. We collected population sampling data for arowana golden red by using 'fish net', 'fish trap', and 'fish scoop-net'. A comparison of satellite images taken in 2017 and 2021 revealed a reduction in swamp area by 664 ha (from 921 to 257 ha) and a decrease in swamp forest by 116 ha (from 264 to 148 ha). The conversion of swamp and swamp forests into oil palm plantations within the AgrCA has significantly diminished the natural habitat of the arowana golden red. Although there has been decreasing in swamp and swamp forests in AgrCA, the water quality in the AgrCA has remained suitable for the life of the arowana golden red. The population of arowana golden red was found to be 14-44 individuals year-1 in 2021-2023 with various sizes. Arowana golden red is most prevalent during the rainy season (July-December). Preserving the remaining swamp and swamp forests is paramount, representing a top priority. Immediate ex-situ conservation efforts are imperative, taking preemptive measures in case the arowana golden red can no longer inhabit its natural habitat.